Characterization and inter-strain variability in ichthyotoxicity of Heterocapsa ovata (Peridiniales, Dinophyceae) from temperate waters of South Australia - Verma, Arjun; Gaiani, Greta; Hoppenrath, Mona; Dorantes-Aranda, Juan Jose; Smith, Kirsty; Kohli, Gurjeet Singh; Wilkinson, Clinton; Hallegraeff, Gustaaf Marinus; Murray, Shauna Ann (Frontiers in Protistology, 2024)
Introduction Harmful algal bloom (HAB)-forming species and populations exhibit substantial intraspecific functional trait variation, which can confer eco-evolutionary advantages. Phenotypic variability among populations can buffer the immediate detrimental effects of environmental fluctuations, with more diverse populations expected to survive changing conditions more efficiently than their uniform counterparts. Methods In February 2014, a mixed fish-killing dinoflagellate bloom occurred in the temperate waters of Coffin Bay, South Australia, causing the death of oysters and fish in the area. The bloom was dominated by Karenia mikimotoi and a cryptic species of Heterocapsa. Twenty-one monoclonal Heterocapsa isolates were established from the site and identified as H. ovata using microscopy and universal ribosomal markers (ITS/5.8S and LSU D1/D3 rDNA regions; SSU and cob were used for amplicon sequencing). These isolates were tested for ichthyotoxicity using a bioassay based on cells from the gills of rainbow trout (Oncorhynchus mykiss). Culture fraction preparations (whole cells, supernatant, and lysed cells) were analyzed to determine ichthyotoxicity levels. Results The highest ichthyotoxicity was observed in lysed cells, with surprisingly high inter-strain variability. This suggests that different strains of H. ovata have varying levels of toxicity. Discussion Results from this study expand our understanding of the adaptive strategies of HAB species and enable predictions of future population dynamics under changing climatic conditions. The substantial phenotypic variability among H. ovatastrains highlights the potential for diverse responses to environmental stressors, underscoring the importance of considering intraspecific variation in ecological and evolutionary studies of HABs.